FOOD AS A WAY TO PREVENT DEPRESSIVE CONDITIONS AND DISORDERS - Halmirzaeva S. S. (Web of Journals Publishing, 2024)
In the modern world, eating food has ceased to be a normal physiological need. This article discusses only the features of the influence of certain foods on the psycho-emotional state of students of the Andijan State Medical Institute, in particular foods rich in tryptophan. According to the results of the survey, there is a tendency for the psycho-emotional state to depend on products containing tryptophan, but it does not depend on its percentage in these products. The choice of products depends on the taste preferences of individuals.
Keywords: products, mood, emotions, depression, serotonin, tryptophan, prevention, health.